The search for scientific information in Central University of Ecuador: reflections from the case of the Faculty of Physical Culture - Rodríguez Torres, Ángel Freddy (2018)
This study aimed to diagnose the participation of the professors at Physical Culture Career in research processes, and the abilities to search for information. This was a cross sectional study, involving 27 teachers of both genders. A questionnaire was administered and the data were analyzed with the SPSS v.22.0. The following results were obtained: 55.6% of the faculty do not belong to a research group, 77.8% have participated in the design of research projects and 74.1% have participated in the execution of research projects. Teachers have difficulties in distinguishing scientific evidences from other types of evidence (62.9%), but they are better prepared to access relevant information in books and search for information electronically. Development of skills related to searching for information is not correlated with the participation in research processes by the faculty. The discussion highlights that excessive scientific production available, makes it difficult to access the most relevant information. It is concluded that although most of the teaching staff does not belong to a research group, more than three-quarters of the teachers have participated in the design and execution of research projects; however they have difficulties in distinguishing scientific evidence